(NrE^X W NAU^NO(B-(NLINGWISTI^ESKOM I DIDAKTI^ESKOM ASPEKTAH (B/s - (NmINAEWA(B, (Nl@DMILA wLADIMIROWNAs; (NnIKOLAEWA(B, (NnINA eWGENXEWNAs; (NbORISENKO(B, (Nt(B.(Ni(B.s ((NmOSKWA (B:s (Nmgu(B,s, 1991)
(NbIBLIOGR(B. (NW PRIME^(B. (NW KONCE GLAWs
(NaWT(B. (NUKAZANY W SODERV(B.s
Keywords: (NrE^EWAQ DEQTELXNOSTXs; (NrE^Xs -- (NwOSPRIQTIEs